Analisis Yuridis Mediasi Sebagai Solusi Alternatif Penyelesaian Sengketa Konsumen Di BPSK (Studi Kasus Bapak I Wayan Vs Pt Optimo Internasional) - Sinaga, Sesilia Faska Tiara Ernawati; Apriani, Rani; Kurniati, Grasia (Peneliti.net, 2024)
The problem in this writing is about how the role of mediation in dispute resolution and how the process of resolving consumer disputes at BPSK through mediation based on a case study of Mr. I Wayan as a consumer against Pt Optimo International as a business actor in Denpasar City. The laws and regulations used in this research are Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution, Law Number 8 of 1999 on Consumer Protection. The conclusion in this paper is that mediation has a role, namely as an alternative form of dispute resolution that grows and develops in line with the human desire to resolve disputes quickly and satisfactorily for both parties, as well as reducing the accumulation of cases in court. Then, the procedure for settlement through mediation at BPSK is contained in Article 31 of Decree of the Minister of Industry and Trade Number 350/MPP/Kep/12/2001. Based on the case of a consumer dispute between Mr. I Wayan Astawa and the company PT Optimo International, this case was brought to BPSK Denpasar City and took the Mediation Path, the mediation process finally reached a peace agreement.